FULBRIGHTER IN THE ANTIPODES. - Murphy, Mary E. (The Accounting Review, 1954)
Abstract The article focuses on the accounting education in Australia. Upto the year 1954, only the University of Melbourne, Melbourne, Victoria, had a well established curriculum of accountancy. A full-time student normally takes four subjects a year. The honors course is a four-year one in which the compulsory subjects are covered in the first two years, after which the student enters the final division, comprising special honors lectures and seminars, with examination at the end of the fourth year of his studies. During this last year he is also required to submit a thesis on a subject within a specialized field of his own choice. The first of these courses is regarded as an introduction to accounting method, with students required to maintain a small set of double-entry records. It covers the theory of accounting and interpretation of transactions, ledger, journal and its subdivisions, trial balance, control accounts and subsidiary ledgers, preparation of reports, balance day adjustments, unsystematized records, non-trading enterprises, partnerships, joint stock companies, closing accounts of vendor, funds statement, departmental accounts, branch accounts, consignments, joint ventures, columnar accounting, analyzed journals and auditing.